Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah terhadap Kinerja dan Motivasi Guru Sekolah Dasar - Aziz, Asep Saepul; Karlimah, Karlimah; Hidayat, Syarip (Universitas Negeri Padang, 2025)
This study aims to evaluate the effect of the transformational leadership style of the principal on teacher motivation and performance at SDN Segugus 1, Sindangkasih Subdistrict, Ciamis Regency. Using a quantitative approach with a survey method, all teachers were included in the population, and the sample was selected purposively. Data were obtained through a closed questionnaire and analyzed using path analysis. The results indicate that transformational leadership style significantly influences teacher motivation (p = 0.000) and performance (p = 0.000), and motivation also significantly influences performance (p = 0.007). Leadership elements such as ideal influence, inspirational motivation, intellectual stimulation, and personal attention were found to promote professionalism and work enthusiasm among teachers. These findings emphasize the importance of effective leadership in improving the quality of educators in elementary schools.